2006
DOI: 10.1634/stemcells.2006-0428
|View full text |Cite
|
Sign up to set email alerts
|

CpG Methylation Profiles of Endothelial Cell-Specific Gene Promoter Regions in Adipose Tissue Stem Cells Suggest Limited Differentiation Potential Toward the Endothelial Cell Lineage

Abstract: In vivo endothelial commitment of adipose stem cells (ASCs) has scarcely been reported, and controversy remains on the contribution of ASCs to vascularization. We address the epigenetic commitment of ASCs to the endothelial lineage. We report a bisulfite sequencing analysis of CpG methylation in the promoters of two endothelial-cell-specific genes, CD31 and CD144, in freshly isolated and in cultures of ASCs before and after induction of endothelial differentiation. In contrast to adipose tissue-derived endothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
59
0
3

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 43 publications
4
59
0
3
Order By: Relevance
“…However, in our study, the methylation status of promoter CpG islands was found to be preserved in critical genes, such as SOX9 and RUNX2, during chondrogenesis. This observation may indicate a retained capability of the mesenchymal progenitor cells to change their differentiation status even after chondrogenesis, since similar observations about adipogenesis of MSCs have been reported (36)(37)(38)(39).…”
Section: Discussionsupporting
confidence: 82%
“…However, in our study, the methylation status of promoter CpG islands was found to be preserved in critical genes, such as SOX9 and RUNX2, during chondrogenesis. This observation may indicate a retained capability of the mesenchymal progenitor cells to change their differentiation status even after chondrogenesis, since similar observations about adipogenesis of MSCs have been reported (36)(37)(38)(39).…”
Section: Discussionsupporting
confidence: 82%
“…[16][17][18] However, the ability of ASCs to undergo direct differentiation to endothelial cells remains contentious. 19 Recent findings suggest that these vessels may arise due to a minute subpopulation of residual committed endothelial cell progenitors that undergoes extensive proliferation and selfassembly to form vascular networks. 16,20 Recently, a few groups have shown promise in the potential of using ASCs 4,21 or fresh adipose stromal vascular fraction (SVF) 22,23 to form vascularized bone.…”
Section: Introductionmentioning
confidence: 99%
“…[72][73][74][75][76] Investigators have continued to pursue the role of CpG methylation in the context of adipogenesis using primary adiposederived stem cells (ASCs) as well as MSCs. [77][78][79] Analysis of the CpG methylation pattern of promoter elements in ASCs finds that while adipocyte-associated genes (lipoprotein lipase, leptin, peroxisome proliferator activated receptor gamma) were hypomethylated, 79 those of endothelial-associated genes (CD31, CD 144) remained stably methylated, 77 suggesting that ASC differentiation along the endothelial pathway is limited. Comparisons between ASC and MSC cell lines have indicated that CpG methylation regulates adipogenic events.…”
Section: B Mesodermal Lineagesmentioning
confidence: 99%